2007
DOI: 10.4321/s0210-48062007000700004
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento de la disfunción del suelo pélvico

Abstract: RESUMENTRATAMIENTO DE LA DISFUNCIÓN DEL SUELO PÉLVICO El periné está formado por elementos músculos-aponeuróticos que se integran bajo el control del sistema nervioso. Su alteración es responsable de patologías uroginecológicas, coloproctológicas y sexuales. Para conseguir su tratamiento exitoso es obligado no olvidar el papel que juega el periné en las mismas.El tratamiento de la disfunción del suelo pélvico agrupa una serie de técnicas y procedimientos conservadores como cambios en hábitos de vida, terapia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…This signal is subsequently used to teach and correct the physiological process, achieving a therapeutic effect (8,11). Biofeedback is considered as an operant conditioning therapy (12).…”
Section: Discussionmentioning
confidence: 99%
“…This signal is subsequently used to teach and correct the physiological process, achieving a therapeutic effect (8,11). Biofeedback is considered as an operant conditioning therapy (12).…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that 71.42% of the patients had improved by the fourth week, and 80% of them had improved by the tenth week of the program. Just as Lorenzo Gómez et al 28 showed improvement of UI symptoms with less than half the number of treatment sessions used in the present study, Pena Outeiriño et al 29 found improvement in women (n=72) with low PMF tone or inability to understand the mechanics of perineal contraction after six 20-minute sessions of electrical stimulation with biphasic currents. However, the rate of improvement reported by the authors (66%) was lower than that of the present study (87.5%).…”
Section: Discussionmentioning
confidence: 89%
“…Para a incontinência de esforço, frequências iguais ou superiores a 50 Hz conseguem ativar o reflexo pudendo. Para a incontinência de urgência, empregam-se frequências entre 5 e 10 Hz, que ativam o reflexo pudendo inibitório do detrusor, levando ao término ou diminuição das contrações involuntárias desse músculo; a largura de pulso oscila de 1 a 5 ms 12,13 . Estudos realizados em humanos, em músculos atrofiados após cirurgias ou de indivíduos sedentários, mostraram que a fisioterapia com a ES aumentou significativamente a proporção das fibras musculares e a força muscular durante uma contração voluntária máxima sustentada, o que apoia nossos dados em relação à musculatura uretral 14,15 .…”
Section: Discussionunclassified